Nature as symbolism of aesthetics in the traditional Malay living environment - Azmin, Aida Kesuma (IIUM Press, 2011)
This section identifies peoples' aspirations towards aesthetical symbolism of nature in their contemporary living environments. It also discovers the level of people's knowledge about their d"relling architecture. According to survey findings, people's perceptions relating to aspects of aesthetics are always associated with nature, and the natural appreciation towards it. Colour, water and carving traditions are attributes of nature that have been transformed into symbolic cultural meanings and cosmological understandings by indigenous societies. They add value and quality to the living environment and manifest the relationship between Man and nature, Man and God, as well as Man and Man. They also act as the catalyst intellectual development and creativity in relation to design, gardens and crafts in the built environment.